Gestão social dos territórios rurais – uma avaliação da experiência no território do Maciço de Baturité - Silva, Antonio Michel Felix (2022)
Territorial development was highly valued in government agendas until mid-2016, including the basic requirements of participation, an appreciation of social control and, consequently, social management as a way of making it effective. The work brings a theoretical discussion as an analysis of the management concept of its social proposal and development in the development policy of territorial development, having as study area the territory of the Maciço do Baturité/CE. The analysis starts from the use of theory beyond the subject, as well as the advances of this issue in the academic environment and still making use of the triangulation technique whose instruments adopted in addition to a closed questionnaire, uses a semi-structured interview with public agents and actors. socially linked to politics. To this end, the debate given by several authors is presented, among which the bibliometric study carried out by Iizuka and Junqueira (2013); the meetings of Tenório (2005), among others.This discussion development is present in three strategies and the first approach to content under construction, presenting a discussion on the topic and the advancement of the issue in the middle concept of social concept. In the second part, I discuss the policy, its institutional framework and the proposed social management cycle. The third part brings the evaluation as a method followed by the reports, evaluations and interviews that subsidize the social management in Maciço do Baturité. The results shown that occurs a political discursive between the public movements that if appropriated from the same terms and spaces, have generated a theoretical field , as well as political power over the issue of social management. It is concluded that the notes of this study are useful to the public, especially to the power society, so that from a consideration of power it provides new alternatives, each civilian and their true sensitivity, provide their own reality in which they intend to change.